2011
DOI: 10.1111/j.1467-9507.2011.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Respect in the Relation of Aggression to Popularity

Abstract: Can aggressive children be popular with peers? Generally, sociometric popularity (liking nominations) has been shown to be negatively associated with aggression, and perceived popularity (popularity nominations) has been shown to be positively associated with aggression. The thesis of the present research was that being respected by peers moderates the relation between aggression and popularity. For both thirdthrough sixth-grade boys (N = 107) and girls (N = 117), perceived popularity by peers was positively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
(78 reference statements)
2
12
0
1
Order By: Relevance
“…Research has already shown that being respected is related to various aspects of children's peer relations across multiple levels. For example, being respected by others and showing respect to others are at the interactional level of social competence, which influence, and are influenced by, other levels, (i.e., individual, relationships, and group; Cohen, Hsueh, Zhou, Hancock, & Floyd, ; Hsueh et al, ; Kuryluk, Cohen, & Audley‐Piotrowski, ). Literature across disciplines supports the finding that being respected by peers is positively related to peer social competence at the individual (Huo & Binning, ), interactional (Langdon & Preble, ), relationship (Hsueh et al, 2005), and group levels (Cohen et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has already shown that being respected is related to various aspects of children's peer relations across multiple levels. For example, being respected by others and showing respect to others are at the interactional level of social competence, which influence, and are influenced by, other levels, (i.e., individual, relationships, and group; Cohen, Hsueh, Zhou, Hancock, & Floyd, ; Hsueh et al, ; Kuryluk, Cohen, & Audley‐Piotrowski, ). Literature across disciplines supports the finding that being respected by peers is positively related to peer social competence at the individual (Huo & Binning, ), interactional (Langdon & Preble, ), relationship (Hsueh et al, 2005), and group levels (Cohen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical results may also suggest a difference. Whereas being respected has been shown to be linked to peer liking (Cohen et al, ) and peer status (Huo & Binning, ; Kuryluk et al, ), as well as social competence (Rubin & Rose‐Kransor, ), showing respect has not been examined in relation to peer relations or social competence.…”
Section: Introductionmentioning
confidence: 99%
“…(© pressmaster/fotolia.com) Beim Zusammenhang von Aggression und Beliebtheit muss man allerdings zwischen Kindern unterscheiden, die in Bezug auf soziometrische Maße beliebt sind, und Kindern, die von den Peers gemocht werden. Kinder, die von den Peers als jemand bezeichnet werden, den sie mögen, sind zwar meistens nicht sonderlich aggressiv, aber Kinder, die man in der Gruppe als statushoch wahrnimmt -und die ebenfalls häufig als "beliebt" "oder cool" etikettiert werden -, werden oft eher als überdurchschnittlich aggressiv eingeschätzt, und sie setzen diese Aggression ein, um ihre Ziele zu erreichen (Hawley 2003;Kuryluk et al 2011;Prinstein und Cillessen 2003). Dieser Zusammenhang zwischen Aggression und wahrgenommener Beliebtheit, den man in gewissem Grad schon in der Vorschule sieht (Vaughn et al 2003), wird in der frühen Adoleszenz besonders stark.…”
Section: Beliebte Kinderunclassified
“…As children enter school, peer adjustment plays an important role in social and cognitive development (Newcomb, Bukowski, & Patee, ). Peers provide children with companionship, support, a sense of belonging, respect, and evaluative feedback regarding their social and academic behaviors that is unique from that provided by adults (Buhrmester & Furman, ; Gest, Rulison, Davidson, & Welsh, ; Kuryluk, Cohen, & Audley‐Piotrowski, ). It is no wonder that the establishment of positive peer relations is important for elementary school children's well‐being or that it is related to the development of social cognitive skills (Rubin et al, ).…”
Section: Introductionmentioning
confidence: 99%